2018
DOI: 10.1002/leap.1198
|View full text |Cite
|
Sign up to set email alerts
|

Internationalization of China's English‐language academic journals: An overview and three approaches

Abstract: This paper presents data regarding the publication of Chinese English‐language journals (CELAJs), building on previously published information to investigate the status, growth, and international penetration of these journals. The article also presents three case studies of CELJs to demonstrate different strategies for achieving internationalization. We find that there has been rapid growth in CELJs between 2006 and 2011 but mostly in the science, technology and medicine disciplines. There are now 435 CELJs, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
0
9
0
1
Order By: Relevance
“…Chinese scholars publish papers in both international and domestic journals (Wang, Chen, Liu, & Hu, ; Xu, Wang, Zhou, & Liu, ; Zhang, Liu, & Wei, ). Many researchers have concluded that it is appropriate to combine both international and domestic databases to measure Chinese research performance (Cui & Zhang, ).…”
Section: Methodsmentioning
confidence: 99%
“…Chinese scholars publish papers in both international and domestic journals (Wang, Chen, Liu, & Hu, ; Xu, Wang, Zhou, & Liu, ; Zhang, Liu, & Wei, ). Many researchers have concluded that it is appropriate to combine both international and domestic databases to measure Chinese research performance (Cui & Zhang, ).…”
Section: Methodsmentioning
confidence: 99%
“…This may discourage scientific innovation. Besides, China has currently committed to developing Chinese English-language scientific journals (Lin & Zhan, 2016;J. Xu, Wang, Zhou, & Liu, 2019).…”
Section: Journal Licensingmentioning
confidence: 99%
“…This may discourage scientific innovation. Besides, China has currently committed to developing Chinese English‐language scientific journals (Lin & Zhan, 2016; J. Xu, Wang, Zhou, & Liu, 2019). However, some scholars believe these ambitions are hindered by the restriction of CN numbers in the journal licensing system (Lin, 2013a, 2013b; Lu, 2010; S. L. Ren et al ., 2018).…”
Section: Key Challenges For the Chinese Publication Systemmentioning
confidence: 99%
“…Ainda sobre esse tema, Xu et al (2019) analisaram estratégias de internacionalização de 435 periódicos científicos chineses e identificaram como sendo as mais relevantes: (a) a inclusão de pesquisadores importantes de outros países no conselho editorial; (b) visibilidade online; (c) conversão de periódico nacional em internacional; e (d) o estabelecimento de parcerias com editoras comerciais internacionais. Entre as editoras comerciais operando em parceria com os periódicos chineses, os pesquisadores identificaram que as três maiores eram: Springer (113 títulos), Elsevier (73) e Wiley (14), sendo que as duas primeiras também predominaram entre os periódicos brasileiros que se associaram a editoras comerciais.…”
Section: Humanasunclassified